2017
DOI: 10.18632/oncotarget.16546
|View full text |Cite
|
Sign up to set email alerts
|

Abce1 orchestrates M-phase entry and cytoskeleton architecture in mouse oocyte

Abstract: ATP-binding cassette E1 (ABCE1) is a member of the ATP-binding cassette transporters and essential for diverse biological events regulating abroad range of biological functions including viral infection, cell proliferation, anti-apoptosis, translation initiation and ribosome biogenesis. Here, we discovered that Abce1 also plays indispensable roles in mouse oocyte meiotic progression. In the present study, we examined the expression, localization, and function of Abce1 during mouse oocyte meiotic maturation. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Defects in spindle assembly and abnormality of chromosome alignments can result in the failure of PBE. (Dumont and Desai 2012;Huang et al 2017;Jiao et al 2017). More importantly, studies have shown that cellular ATP level is a vital event to ensure the normal bipolar spindle assembly and the decrease of ATP content results in various spindle defects and chromosome alignment anomaly (Eichenlaub-Ritter et al 2004;Zhang et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Defects in spindle assembly and abnormality of chromosome alignments can result in the failure of PBE. (Dumont and Desai 2012;Huang et al 2017;Jiao et al 2017). More importantly, studies have shown that cellular ATP level is a vital event to ensure the normal bipolar spindle assembly and the decrease of ATP content results in various spindle defects and chromosome alignment anomaly (Eichenlaub-Ritter et al 2004;Zhang et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One of the hallmarks of the metastatic process is altered cellular motility [12], a complex process requiring dramatic remodeling of the cell cytoskeleton. Because accumulating evidence indicates that ABCE1 plays an important role in cytoskeleton regulation [1315], PubMed curation was used to filter the remaining eleven genes (excluding ABCE1) by their association with cytoskeleton organization. We found that LCP1 is an actin binding protein that participates in cytoskeleton remodeling [1618].…”
Section: Resultsmentioning
confidence: 99%
“…Spindle assembly and chromosome segregation are two indispensable events during the progress of meiosis. Defective morphology of spindles and abnormal chromosome alignments could result in aneuploid gametes or the failure of meiosis (Ma et al, 2014;Jiao et al, 2017;Han et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Spindle assembly and chromosome segregation are both vital courses to keep genomic stability during oocyte meiosis. Errors in these two processes can lead to the failure of meiosis or the generation of aneuploidy (Ma et al, 2014;Jiao et al, 2017;Han et al, 2015). Moreover, human pregnancy loss has strong correlation with fetal aneuploidy which can be induced by defective spindle structure and abnormal chromosome segregation (Webster et al, 2017).…”
Section: Introductionmentioning
confidence: 99%